Pemenuhan Hak Politik Penyandang Disabilitas Sesuai Dengan Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas oleh Komisi Pemilihan Umum (KPU) Kota Yogyakarta - Mugi Riskiana Halalia (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2017)
The result of the research shows that the Election Commission of YogyakartaCity as the organizer of General Election in Yogyakarta City has made efforts to fulfillthe political rights for people with disabilities in Yogyakarta City in the implementationof general election. The efforts made by the Yogyakarta City Election Commission havebeen in accordance with Law No. 8 of 2016 on Persons with Disabilities by upholdingequal values and equal opportunity for persons with disabilities to participate inpolitical life. KPU Kota Yogyakarta in order to fulfill the political rights of disabilitasin the General Election to carry out such efforts, to maximize voter data collection todisabilitas people, to provide socialization and simulation on equal political rights fordisabilitas people and services to disabilitas people in elections, involvement of disabilitaspeople by recruiting Democratic Volunteers, some of whom are persons with disabilitiesand involving persons with disabilities as officers in the electoral structure, as well asproviding accessible facilities and infrastructure of TPS.